Pengelompokan Tingkat Kecerdasan berdasarkan Kecerdasan Ganda (Multiple Intelligence) Anak di Sekolah Menggunakan Metode Clustering: Studi Kasus: SD Islamiyah - Adinda Maudia Savira; Relita Buaton; Juliana Naftali Sitompul (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Education is an important place for students to develop their potential based on their intelligence. Multiple intelligences offer an approach that considers the various potentials of students in the learning process. SD Islamiyah, as an educational institution with a vision to produce intelligent and creative generations, faces challenges in delivering learning that meets the needs of students. To address this issue, a system is needed that can analyze and group students based on their intelligence levels using the clustering method. This study is inspired by the application of data mining in the educational context, particularly in adapting the clustering method as applied in other related research. Previous research has demonstrated the success of the clustering method in accurately grouping data, as seen in studies related to flood warnings and cesarean operations. By applying a similar approach, this research aims to assist SD Islamiyah in identifying and grouping students based on their potential, thereby facilitating a more effective learning process tailored to the individual needs of students. The results of this study are expected to contribute positively to improving the quality of education at SD Islamiyah and provide a foundation for the development of more advanced decision support systems in the future